IMPACT OF SEWAGE ON PLANKTON PRODUCTION - JANA, DEBASMITA; ROUT, SANGRAM KESHARI; TRIVEDI, RAMAN KUMAR; DAS, BIPUL KUMAR; BEHERA, LOPAMUDRA (Journal of the Inland Fisheries Society of India, 2021)
Waste water particularly the sewage water is a readily available biodegradable nutrient rich resource and reuse of the effluent can enhance the water productivity through plankton production. A study was carried out to assess the abundance and fluctuations of plankton and productivity in different concentration (25%, 50%, 75% and 100%) of sewage water. Selected relevant water parameters such as temperature, pH, dissolved- oxygen (DO), alkalinity, hardness, ammonia -nitrogen (NH3 -N), phosphate- phosphorous (PO4 -P), nitrate-nitrogen (NO3 -N), biological oxygen demand (BOD), chemical oxygen demand (COD), total solid (TS) and total dissolved solid (TDS) in sewage effluent in different treatments were monitored along with certain biological parameters viz. plankton production and primary productivity. The primary productivity and plankton production were observed to be significantly higher (P<0.05) in 100% concentrated sewage water than the other treatments. Key words: Waste water, productivity, plankton